Tanggung Jawab Sosial Perusahaan Pada Industri Rokok - Ahmad Rizal Solihudin; Bagus Gumelar (BALANCE: Economic, Business, Management and Accounting Journal, 2018)
ABSTRACT This study aims to map and analyze the performance of corporate social responsibility in the cigarette industry. This is done to assess the extent of the cigarette industry's contribution to the social aspects with the company's value benchmark. This research is a quantitative research using content analysis method. The unit of analysis in this study is the annual report of tobacco companies listed on the BEI. The results showed that market valuation had a significant effect on the performance of the social responsibility of cigarette companies in Indonesia on aspects of labor and human rights. In addition, the distribution of social responsibility contributions was less optimal so there needed to be rules that technically direct the activities of tobacco companies so that the benefits are acceptable to all stakeholders optimally. Keywords : cigarette, stakeholder, social responsibility.Correspondence to : arsolihudin@gmail.com ABSTRAK               Penelitian ini bertujuan memetakan dan menganalisis kinerja tanggung jawab sosial perusahaan padaindustri rokok.Hal ini dilakukan untuk menilai seberapa jauh kontribusi industri rokok pada aspek sosial dengan tolak ukur nilai perusahaan. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode analisis konten. Unit analisis dalam penelitian ini adalah laporan tahunan perusahaan rokok yang terdaftar pada BEI. Hasil penelitian menunjukkan bahwa penilaian pasar berpengaruh signifikan terhadap kinerja tanggung jawab sosial perusahaan rokok di Indonesia pada aspek tenaga kerja dan hak asasi manusia.Selain itu, pemerataan kontribusi tanggung jawab sosial kurang optimal sehingga perlu ada aturan yang secara teknis mengarahkan aktifitas tanggung jawab sosial perusahaan rokok agar manfaat dapat diterima semua stakeholder secara optimal.Kata kunci                   :rokok;stakeholder;tanggung jawab sosial.Korespondensi             : arsolihudin@gmail.com